Evaluating Climate Change Action for Sustainable Development - Uitto, Juha I.; Puri, Jyotsna; van den Berg, Rob D. (Springer Nature, 2017)
Climate Change; Sustainable Development; Climate Change/Climate Change Impacts; Environmental Management